A Prostate Specific Antigen Immunosensor Based on Biotinylated‐Antibody/Cyclodextrin Inclusion Complex: Fabrication and Electrochemical Studies. Issue 12 (10th October 2017) - Mousavi, Mir F.; Amiri, Masoud; Noori, Abolhassan; Khoshfetrat, Seyyed Mehdi
Abstract: Immobilization of biomolecules with a proper orientation is considered as a basis for diverse biotechnological applications. Herein, we report a host‐guest inclusion complexation between β‐cyclodextrin (β‐CD) and biotin as a versatile approach for the immobilization of biomolecules. As a practical application, a sandwich‐type electrochemical immunosensor was designed for the determination of prostate specific antigen (PSA). The immunosensor was fabricated by in situ electropolymerization of poly(N‐acetylaniline) onto a rGO‐modified Pt electrode. Then, β‐CD was covalently grafted onto the over‐oxidized polymer backbone. For improving the efficiency of the assay, AuNPs were casted on the polymeric film, on the surface of which thionine (TH) as an electron mediator was covalently immobilized. Using a host‐guest inclusion complexation between β‐CD and biotin, a β‐CD/biotin‐Ab1 /PSA/Ab2 ‐horseradish peroxidase (HRP) sandwich was formed on the electrode surface. The analytical signal was produced via electrochemical reduction of THox, generated by biocatalytic oxidation of the THred in the presence of HRP/H2 O2 . Under optimal conditions, the proposed sensor responded linearly to PSA in the range from 10.0 pg mL −1 to 25.0 ng mL −1, with a low detection limit of 6.7 pg mL −1 (S/N=3). Kinetic parameters of the interaction of β‐CD with Ab1 were also investigated. Finally, the applicability of the immunosensor was successfully investigated for the detection of PSA in human serum samples. Abstract :